Tenor Analysis of Selected Short Stories by Tariq Rahman: Applying Halliday’s Interpersonal Metafunction - Batool, Muazzma; Rubab, Iram; Ajmal , Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
This study aims at exposing the role relationship among the characters and the way they make their interpersonal meaning (tenor) in the selected short stories which is concerned with clauses as exchanges. Since language involves interactions where the participants either initiate or respond to the act of giving (means inviting to receive) or demanding (means inviting to give) for goods-and-services or information, therefore, the principle grammatical system for this is the Mood network comprising of a choice between imperative and indicative. If indicative is chosen, there is a choice between declarative and interrogative. These choices are realized by manipulating the Mood elements. For analyzing the data, the design of this research uses both the quantitative and qualitative approaches. The data for this study have been collected from 2 short stories by Tariq Rahman. The findings reveal that the imperative mood is less used as compared to the declarative mood which is dominant in selected short stories with a little bit of interrogative mood for indicating the participants’ attitude of either giving or receiving more information from their counterparts. The contact among the participants is most of the time involved but sometimes uninvolved to show the power of the dominant social members. The analysis of affect highlights that the effect of the dominant social members’ conversation on the less powerful people remains almost positive because they are unable to challenge the authority of the powerful people but sometimes the affect is negative when the poor social members protest against the authority of the powerful people for getting rid of their violence which lead them to get more aggression.